Reality Shows:The New Marketing Tool - Sengupta, Debashish (Indian Journal of Marketing, 2009)
Reality Shows on Indian television have become the latest craze. They are fast replacing the daily soaps as ’number one’ in terms of popularity. The high TRPs for these shows have made them a must for almost every channel; who in turn are airing one or the other kind of such shows. There have been both bouquets and brickbats for such type of shows but surprisingly even controversy has contributed to their popularity. Marketers have been quick to cash-in on the popularity of these shows. The reality shows in India have opened floodgates for the marketers. Everyone is making a lot of money and no one seems to be complaining. And why not! After all it is giving gains to everyone. But popularity of these shows doesn’t appear to be the only reason as to why marketers are preferring reality shows to be their new marketing tool. This paper attempts to study some of the very obvious reasons why marketers find reality shows very attractive marketing vehicle. Initially it also tries to find out the reasons for the high-popularity of reality-shows and also look at some examples where marketers have gained heavily because of such shows.